Analisis Keterlibatan Fashion dan Gaya Hidup Berbelanja terhadap Pembelian Impulsif pada Distro Platt Mars Cabang Kota Sukabumi - Rayyisa Nurul Haq; Acep Samsudin; Faizal Mulia Z (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study was to analyze the effect of fashion and lifestyle involvement on impulsive purchases of distro platt mars. The method in this study uses a type of probability sampling, including simple random sampling. The analysis technique used is the validity test, reliability test, multiple linear regression analysis including the coefficient of determination test, multiple correlation coefficients, and testing the hypothesis using the test simultaneously (F test). The results of the test of the coefficient of determination seen from the value (Adjusted R2) of 0.325 can be interpreted that the influence of Fashion Involvement and Shopping Lifestyle on Impulsive Purchases is 32.5%. The remaining 67.5% is influenced by other factors outside this study. Based on the multiple correlation coefficient test seen from the R value of 0.582 shows that there is a strong relationship between fashion involvement and shopping lifestyle with impulsive purchases. Based on the F test the probability value sig. 0,000 <0.05. Conclusions, together with Fashion Involvement (X1) and Shopping Lifestyle (X2) significantly influence Impulsive Purchase (Y). Keywords: Fashion Involvement, Shopping Lifestyle, Impulsive Purchasing